Pengaruh Disiplin Kerja, Kepemimpinan Demokratis dan Budaya Organisasi Terhadap Kinerja Pegawai Pada Kantor Badan Penanggulangan Bencana Daerah ( BPBD ) Kabupaten Alor - Theresia Lounggina Luisa Peny (Peneliti.net, 2023)
This study aims to determine the effect of work discipline, democratic leadership and organizational culture on the performance of employees of the Alor Regency Regional Disaster Management Agency, either partially or simultaneously. Respondents of this study were 106 employees. Data collection using questionnaires, observation, and documentation studies. The data is then analyzed using the t-test to determine the partial effect and the F-test to determine the simultaneous effect on performance with the results of the study being: 1) The variables of work discipline, democratic leadership, organizational culture and employee performance have a Pearson product moment correlation value which is above the limit of 0.3 for the validity test. 2) The variables of work discipline, democratic leadership, organizational culture and employee performance have a chronbah alpha value which is above the limit of 0.6 for the reliability test. 3) The variables of work discipline, democratic leadership, organizational culture and employee performance have a test value for each classic assumption test that is above alpha and passes the classic assumption test. 4)There is an influence of Work Discipline on Employee Performance at the Regional Disaster Management Agency Office of Alor Regency, as evidenced by the significance value of the t test which is 0.000 which is smaller than the research alpha value of 5% (0.05) 5)There is an influence of Democratic Leadership on Employee Performance at the Regional Disaster Management Agency Office of Alor Regency, as evidenced by the significance value of the t test, which is 0.000, which is smaller than the research alpha value, which is 5% (0.05) 6)There is an influence of Organizational Culture on Employee Performance at the Regional Disaster Management Agency Office of Alor Regency, as evidenced by the significance value of the t test, which is 0.000, which is smaller than the alpha value of the study, which is 5% (0.05) 7)There is an influence of Work Discipline, Democratic Leadership and Organizational Culture on Employee Performance at the Regional Disaster Management Agency Office of Alor Regency, as evidenced by the significance value of the F test which is 0.000 which is smaller than the research alpha value of 5% (0.05) From the results of the research and research conclusions, the research team suggested to Respondents (employees of the Alor Regency Regional Disaster Management Agency) that employees are expected to be able to maintain the performance of employees who have been well organized to date, while continuing to improve themselves considering various changes in work situations during the pandemic as is currently the case. Suggestions are also given to the Head of the Alor Regency Regional Disaster Management Agency, so that the leaders who have nurtured and built the values of work discipline and organizational culture that are well ingrained in this scope of work can be maintained and continue to provide enthusiasm, motivation and innovation for the development of good employee performance. much better and overall service performance.